The impact of employee retention on performance among Cosmopoint colleges employees in Peninsular Malaysia / Che Sazlina Che Ibrahim - Che Ibrahim, Che Sazlina (2020)
The retention of employees has been a crucial part of the development and accomplishment of the organization’s goals and objectives. Loss of talented employees results in a drop in performance, therefore, force the organization to improve their retention strategies. For this reason, this study focuses on the relationship between retention and employee performance at Cosmopoint Colleges in Peninsular Malaysia. The objective is to measure the relationship between employee retention factors with employee performance. The study using quantitative data analysis and descriptive statistics. The sample under this study was 127 employees of Cosmopoint Colleges and the questionnaire was distributed to all nine branches of Cosmopoint Colleges throughout Peninsular Malaysia. A set of questionnaires were used which consists of three sections; section A demographic factor, section B consists of factors influencing employee retention and section C focuses on employee performances. Data were analyzed by using SPSS version 22.0. The sampling technique used in this study was stratified random sampling. The analysis used for this study includes descriptive, correlation and multiple regression. The element of retention that examined in this study consists of employee empowerment, training and development, compensation, performance appraisal, and employee commitment. Employee performance is measured by the use of performance indicators which are quality and quantity of work, absenteeism, cooperation, and dependability. The findings of the study revealed a positive relationship between the dependent variable (employee performance) and independent variables (employee empowerment, training and development, employee compensation, performance appraisal, and employee commitment).